2005
DOI: 10.1007/s11630-005-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase invariant proper orthogonal decomposition for the study of a compressed vortex

Abstract: We propose here an experimental investigation of a vortex submitted to a radial perturbation while being compressed. This experiment reproduces a model situation of the complex flows that take place in a real engine cylinder. An isolated tumbling flow is first submitted to an injection of fluid and then compressed and measurements are realised by Particle Image Velocimetry (PIV). The Proper Orthogonal Decomposition is known to be an unbiased method to identify the coherent structures of turbulent flows. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The third (and last) step is the two-dimensional (2D) spline interpolation of the re-scaled data, presently on the re-mapped coordinates, onto the reference grid 13,26,27…”
Section: Relevance Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The third (and last) step is the two-dimensional (2D) spline interpolation of the re-scaled data, presently on the re-mapped coordinates, onto the reference grid 13,26,27…”
Section: Relevance Indexmentioning
confidence: 99%
“…We note three major differences distinguishing the present three-step procedure from similar steps taken in previous phase-invariant POD analyses. 16,17,2628 These differences are rooted in the disparate purpose of yielding a metric for comparing the directional similarity between a pair of vector fields (for the present analysis) versus generating a set of phase-invariant POD modes that span the tumble flow field over multiple crank angles (in previous studies).…”
Section: Relevance Indexmentioning
confidence: 99%
“…It was concluded that the cyclic variations increase during the compression process and at the end of the compression stage, they may decrease to reach to those obtained during the intake process. Moreau et al [23] studied an experimental investigation of a vortex submitted to a radial perturbation while being compressed. An isolated tumbling flow was first submitted to an injection of fluid and then compressed and measurements were realized by PIV.…”
Section: Introductionmentioning
confidence: 99%